Sedimentological evidence for pronounced glacial-interglacial climate fluctuations in NE Tibet in the latest Pliocene to early Pleistocene - Lu, Yin; Dewald, Nico; Koutsodendris, Andreas; Kaboth-Bahr, Stefanie; Rösler, Wolfgang; Fang, Xiaomin; Pross, Jörg; Appel, Erwin; Friedrich, Oliver (Paleoceanography and paleoclimatology, 2020)
The intensification of Northern Hemisphere glaciation (iNHG) and uplift of the Tibetan Plateau have been argued to be among the main drivers of climate change in midlatitude Central Asia during the Pliocene/Pleistocene. While most proxy records that support this hypothesis are from regions outside the Tibetan Plateau (such as from the Chinese Loess Plateau), detailed paleoclimatic information for the plateau itself during that time has yet remained elusive. Here we present a temporally highly resolved ( 500 years) sedimentological record from the Qaidam Basin situated on the northeastern Tibetan Plateau that shows pronounced glacial-interglacial climate variability during the interval from 2.7 to 2.1 Ma. Glacial (interglacial) intervals are generally characterized by coarser (finer) grain size, minima (maxima) in organic matter content, and maxima (minima) in carbonate content. Comparison of our results with Earth's orbital parameters and proxy records from the Chinese Loess Plateau suggests that the observed climate fluctuations were mainly driven by changes in the Siberian High/East Asian winter monsoon system as a response to the iNHG. They are further proposed to be enhanced by the topography of the Tibetan Plateau and its impact on the position and intensity of the westerlies.
Gesehen am 30.03.2021